2014
DOI: 10.1111/1758-2229.12192
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic bicarbonate assimilation is the main process of de novo organic carbon synthesis in hadal zone of the Hellenic Trench, the deepest part of Mediterranean Sea

Abstract: Ammonium-oxidizing chemoautotrophic members of Thaumarchaea are proposed to be the key players in the assimilation of bicarbonate in the dark (ABD). However, this process may also involve heterotrophic metabolic pathways, such as fixation of carbon dioxide (CO2) via various anaplerotic reactions. We collected samples from the depth of 4900 m at the Matapan-Vavilov Deep (MVD) station (Hellenic Trench, Eastern Mediterranean) and used the multiphasic approach to study the ABD mediators in this deep-sea ecosystem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 75 publications
10
27
0
Order By: Relevance
“…Taylor et al ., ; Manganelli et al ., ; Reinthaler et al ., ), thus being highly comparable to organoheterotrophic production rates. It has also been calculated that the amount of inorganic carbon fixed in the dark portion of the water column is in the same range of the one utilized by phototrophic microorganisms in the epipelagic zone (Yakimov et al ., ), thus strengthening the idea of the global ocean as a previously‐underestimated sink of CO 2 .…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Taylor et al ., ; Manganelli et al ., ; Reinthaler et al ., ), thus being highly comparable to organoheterotrophic production rates. It has also been calculated that the amount of inorganic carbon fixed in the dark portion of the water column is in the same range of the one utilized by phototrophic microorganisms in the epipelagic zone (Yakimov et al ., ), thus strengthening the idea of the global ocean as a previously‐underestimated sink of CO 2 .…”
Section: Introductionsupporting
confidence: 58%
“…Furthermore, in the last decade, a growing amount of data have shown that inorganic carbon fixation in the dark ocean via chemosynthetic processes (Herndl et al ., ) and anaplerotic reactions (Yakimov et al ., ) occurs at measurable rates. Chemosynthesis is mainly performed by ammonia‐oxidizing members of the phylum Thaumarchaeota although several metabolic pathways (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our incubations were performed for a maximum of 48 h and previous studies have shown that incubation times shorter than one to 2 weeks seem to prevent labeling of heterotrophic organisms due to cross-feeding (Knief et al, 2003). Therefore, our experiments are likely to have primarily targeted autotrophic microorganisms, but co-assimilation of CO 2 by autotrophs and active members of the heterotrophic community, including thermo- or mesophilic Chloroflexi , cannot be fully excluded (e.g., Roslev et al, 2004; Yamada et al, 2006; Wegener et al, 2012; Yakimov et al, 2014; Schubotz et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Samples were filtered through sterile 0.2-μm cellulose acetate membrane filters (SM 16534 K, Sartorius Minisart, Goettingen, Germany ) under low pressure, high-445 purity N2, and the filtered samples were stored in amber glass bottles at 4 °C in the dark until subsequent analysis. DOC measurements were carried out with a Shimadzu 5000A TOC Analyzer (Shimadzu, Kyoto, Japan) as described by [25], and concentrations were calculated according to [26].…”
Section: Sampling Site and Sampling Proceduresmentioning
confidence: 99%